Comparative proteomics of Listeria monocytogenes strains of food and clinical origin reveals strain-specific adaptation mechanisms - Krasteva, Ivanka; Schirone, Maria; Di Pancrazio, Chiara; Manocchia, Francesco; D'Onofrio, Federica; Maggetti, Marta; Perletta, Fabrizia; Pomilio, Francesco; Bruno, Gianfranco; Torresi, Marina; Centorotola, Gabriella; Paparella, Antonello; et al. (Frontiers in Microbiology, 2025)
Listeria monocytogenes is a foodborne pathogen capable of surviving in diverse environments, including food-processing settings and the human host. This study compared the proteomic profiles of two Listeria monocytogenes strains grown at 37 °C to simulate host-associated conditions: a hypovirulent, food-derived strain and a hypervirulent strain isolated from a human clinical sample. This approach enabled the identification of temperature-induced changes in virulence factors, providing valuable insights into molecular determinants of pathogenicity and potential intervention strategies. Mass spectrometry identified 954 proteins, 642 of which were predicted to be immunogenic. Among these, 128 were unique to the food-derived strain (F), and 29 were specific to the clinical strain (H). Functional analysis revealed that F-specific proteins were primarily involved in terpenoid backbone biosynthesis and the production of secondary metabolites, processes associated with membrane integrity, stress resistance, and metabolic adaptation. In contrast, H-specific proteins were related to acid resistance and bacteriophage-associated functions. Although the number of H-specific immunogenic proteins was insufficient for statistically significant enrichment analysis, six highly interconnected proteins were identified. These results suggest that L. monocytogenes undergoes targeted proteomic remodeling under host-mimicking conditions, facilitating its transition from a food contaminant to invasive pathogen. The identification of immunogenic, strain-specific proteins enhances our understanding of bacterial adaptation and virulence, with important implications for diagnostics, surveillance, and targeted mitigation efforts.